PREDICTORS OF COLECTOMY IN HOSPITALISED PATIENTS WITH ACUTE SEVERE COLITIS. (8th June 2013) - Gibson, D J; Rafter, N; Keegan, D; Byrne, K; Martin, S; O'Connell, P R; Winter, D C; Hyland, J M; Mulcahy, H E; Cullen, G; Doherty, G A
Abstract : Introduction: 20–30% of patients with ulcerative colitis (UC) will have a colectomy during their disease course. This percentage increases to 40% in patients admitted with acute colitis. Aims/Background: To assess if clinical or laboratory parameters on admission can identify patients who will require colectomy on that hospital admission. Method: This was a retrospective review of all patients admitted with a principle diagnosis of UC in a tertiary referral centre between January 2010-November 2011. Patients admitted electively either for endoscopy or UC related surgery were excluded. Results: 91 patients were identified with a principal discharge diagnosis of UC; 39 patients were excluded (elective admission for surgery or endoscopy). 52 patients hospitalised with acute severe colitis were considered eligible for further study. The majority were male; M:F ratio=36:16. Median age was 47. 13 of 52 patients required colectomy during that admission(25%). 17 patients had thrombocytosis (platelets >400) on admission. 25 patients were anaemic (males Hb <13, females Hb <11.5) on admission and 22 patients had albumin level <30 on admission. Neither thrombocytosis (p=0.42) nor anaemia (p=0.56) were predictive of need for surgery. However, in patients who were significantly hypoalbuminaemic (albumin <30) on admission, colectomy was more likely (p=0.026), by Fisher's exact test. Mean CRP on admission was statistically higher in those requiring surgery(103.1 vs 46.9 p=0.03). 2/3 patients who had a CRP>50 combined with albumin <30 at admission required colectomy. Conclusion: In our cohort, raised CRP and significant hypoalbuminaemia on admission were associated with need for colectomy on the same hospital admission. These markers help to categorise patients into high risk who warrant early surgical assessment.